2010
DOI: 10.1007/s11306-010-0249-0
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope resolved metabolomics of lung cancer in a SCID mouse model

Abstract: We have determined the time course of [U-13 C]-glucose utilization and transformations in SCID mice via bolus injection of the tracer in the tail vein. Incorporation of 13 C into metabolites extracted from mouse blood plasma and several tissues (lung, heart, brain, liver, kidney, and skeletal muscle) were profiled by NMR and GC-MS, which helped ascertain optimal sampling times for different target tissues. We found that the time for overall optimal 13 C incorporation into tissue was 15-20 min but with substant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
174
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 97 publications
(182 citation statements)
references
References 44 publications
8
174
0
Order By: Relevance
“…Transformed cells from different origins typically up-regulate both glucose and glutamine consumption as sources of metabolic energy and as precursors for biosynthesis of macromolecules (13,27). The MYC oncogene, which plays a critical role in many human cancers, is considered a master regulator of cell metabolism and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Transformed cells from different origins typically up-regulate both glucose and glutamine consumption as sources of metabolic energy and as precursors for biosynthesis of macromolecules (13,27). The MYC oncogene, which plays a critical role in many human cancers, is considered a master regulator of cell metabolism and proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…To detect plasma level of 13 C 18 -OA, mice were given 13 C 18 -OA as above and blood was collected from tail snip either before (0h), or 1, 2 and 3h after gavage. Lipid was extracted from proximal intestines and plasma 42 and 13 C 18 -OA levels were determined by direct infusion nanospray FT-MS (Orbitrap Fusion ™ Tribrid ™ Mass Spectrometer, Thermo Scientific, Waltham, MA) using a modification of a previous method 43 . Briefly, aliquots of the lipid extracts were diluted twenty-fold in isopropanol:chloroform:methanol (4:2:1), introduced into the TriVersa NanoMate® (Advion, Inc., Ithaca, NY) and analyzed on the Orbitrap Fusion in negative ion mode to estimate the appropriate amount of d34-OA to spike.…”
Section: Methodsmentioning
confidence: 99%
“…13 C abundance of labeled metabolites was calculated from the ratio of the peak areas of the satellite peaks to the total peak intensity according to the equation F=I 13C_satellites /I 13C_satellites +I 12C_central peak , where I is the peak area. 29, 30 We observed that the satellite at 5.36 ppm was often difficult to deconvolve because of partial overlap with the allantoin peak; its integral value was, therefore, obtained from the symmetric satellite peak at 5.08 ppm. Breathing and body temperature were monitored during MRI (SA Instruments, Inc., Stony Brook, NY) and maintained around 30 breaths per minute and 37°C, respectively.…”
Section: Dc/floxmentioning
confidence: 99%